2023
DOI: 10.1101/2023.04.20.537689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation of dichromatin organization along regional centromeres

Abstract: SummaryThe focal attachment of the kinetochore to the centromere core is essential for genome maintenance, yet the highly repetitive nature of human centromeres limits our understanding of their chromatin organization. We demonstrate that single-molecule chromatin fiber sequencing can uniquely resolve chromatin organization within centromeres at single-molecule and single-nucleotide resolution. We find that the centromere core contains a dichotomous chromatin organization not found elsewhere in the genome, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…This attribute is also reflected in our tomograms where we observe kinetochores of varied size and with varied distribution of kinetochore complexes. Specifically, the finding that CENP-A occupancy is often split between multiple regions within a single centromere (Altemose et al, 2022a; Dubocanin et al, 2023; Gershman et al, 2022; Logsdon et al, 2024; Sacristan et al, 2022) is consistent with our own observation that some kinetochores are comprised of a single chromatin clearing whereas others are comprised of 2-3 clearings. Each of the clearings likely corresponds to a region on the linear DNA sequence with a high local density of CENP-A nucleosomes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This attribute is also reflected in our tomograms where we observe kinetochores of varied size and with varied distribution of kinetochore complexes. Specifically, the finding that CENP-A occupancy is often split between multiple regions within a single centromere (Altemose et al, 2022a; Dubocanin et al, 2023; Gershman et al, 2022; Logsdon et al, 2024; Sacristan et al, 2022) is consistent with our own observation that some kinetochores are comprised of a single chromatin clearing whereas others are comprised of 2-3 clearings. Each of the clearings likely corresponds to a region on the linear DNA sequence with a high local density of CENP-A nucleosomes.…”
Section: Discussionsupporting
confidence: 90%
“…The three-dimensional visualization of the kinetochore we present here complements recent one-dimensional DNA maps of the chromatin landscape of the centromere locus (Altemose et al, 2022b; a; Dubocanin et al, 2023; Gershman et al, 2022; Logsdon et al, 2021; Miga et al, 2020). Areas of CENP-A occupancy coincide with regions of reduced CpG methylation termed centromere dip regions (Altemose et al, 2022a; b; Gershman et al, 2022; Logsdon et al, 2021; Miga et al, 2020), and Fiber-Seq of centromeres revealed these same regions to be highly physically accessible, forming the most accessible chromatin domain in the human genome (Dubocanin et al, 2023). These DNA sequencing-based results align remarkably well with our findings where tomograms show kinetochore complexes clustered within a distinct clearing space composed of open chromatin.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In humans, where the spacing between CENP-B box position is 171 bp in α-satellite DNA, CENP-A also has a specific favored position (relative to the more heterogeneous positioning of conventional nucleosomes harboring histone H3), but it is located between CENP-B boxes (40). Furthermore, recent analysis of single-molecule chromatin fiber sequencing data suggests that the CENP-B occupancy may phase nucleosomes on α-satellite DNA (41). In considering M. musculus centromeres, we considered two possibilities.…”
Section: Positioning Of Cenp-a Nucleosomes On the Minor Satellite Is ...mentioning
confidence: 99%
“…For example, with single-molecule chromatin fiber sequencing (Fiber-seq) prior to DNA extraction permeabilized cells are treated with a non-specific N6-methyladenine methyltransferase (m6A-MTase), which stencils the architecture of each chromatin fiber onto its underlying DNA molecule in the form of m6A-modified bases, which can be directly read out during standard Single Molecule, Real-Time (SMRT) sequencing. Furthermore, recent advances in Fiber-seq enable the co-identification of both accurate chromatin features 16 and CpG methylation along each sequenced read 17 , providing genomic sequence, CpG methylation, and chromatin epigenetic information in the same sequencing run. Finally, long-read full-length transcript sequencing is emerging as a powerful tool for resolving the transcript impact of genetic variants 18, 19 , and recent cDNA concatenation workflows for processing full-length transcript data (MAS-Seq) 20 provide an order-of-magnitude higher throughput identification of full-length transcript data.…”
Section: Introductionmentioning
confidence: 99%